ANALISIS INTELLECTUAL CAPITAL TERHADAP SUSTAINABLE GROWTH RATE DENGAN FINANCIAL PERFORMANCE SEBAGAI MEDIASI (Accounting Study Program, Universitas Ciputra Surabaya, 2022)
This study aims to determine the effect of intellectual capital (IC) on sustainable growth rate (SGR) with financial performance proxied by return on assets (ROA) as a mediation. This research is a quantitative research. The population in this study is the index of Kompas 100 companies listed on the Indonesia Stock Exchange (IDX). Sampling using purposive sampling method with several criteria, obtained a sample of 42 companies. This study uses secondary data originating from the company’s financial statements from 2014 to 2019. The results of this study include (1) IC has a significant positive effect on SGR, (2) IC has a significant positive effect on ROA, (3) ROA has a significant positive effect on SGR, and (4) ROA can mediate the relationship between IC and SGR. Keywords: IC, SGR, ROA, Kompas 100.